3′ RACE Walking along a Large cDNA Employing Tiered Suppression PCR. (April 2003) - Park, Daniel J.; Pask, Andrew J.; Renfree, Marilyn B.; Graves, Jennifer A. Marshall
Large genes present particular cloning difficulties, especially when expressed at relatively low levels. We describe a novel method, termed 3′ rapid amplification of cDNA ends (RACE) walking, for the rapid determination of unknown 3′ flanking sequence of a large cDNA. The technique is a derivative of the anchored PCR 5′ RACE procedure but includes a specific and limited second-strand cDNA synthesis and a tiered "panhandle" suppression of nonspecific products. The method generated 900 bp of new sequence for the large tammar wallaby ATRY gene in two easy steps, in which standard 3′ RACE and PCR-based cDNA library walking proved unsuccessful. This robust approach represents a new tool for isolating unknown sequence under challenging cloning scenarios such as poor library representation, long coding regions, long 3′ untranslated regions, and difficult template regions.